Two Celebrated Classical Problems in Geometric Constructions (Jurnal Matematika, Statistika dan Komputasi, 2020)
The main topic of this paper is about two celebrated classical problems in geometric constructions where the only allowed instruments are compass and ruler with no scale. Two such problems are (1) trisecting an angle, and (2) doubling the cube. In addition, we also study about the construction of 7-gon and 10-gon.